2016
DOI: 10.1007/s10620-016-4097-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physician Perspectives on Hepatitis C Management in the Era of Direct-Acting Antiviral Therapy

Abstract: Background Primary care physicians (PCPs) play a critical role in the care cascade for patients with chronic hepatitis C (CHC). Aim To assess PCP knowledge and perspectives on CHC screening, diagnosis, referral, and treatment. Methods An anonymous survey was distributed to PCPs who participated in routine outpatient care at our hospital. Results Eighty (36 %) eligible PCPs completed the survey. More than half were females (60 %) aged 36–50 (55 %) from family (44 %) or internal (49 %) medicine. Overall, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 16 publications
4
44
0
1
Order By: Relevance
“…Specialists were the most comfortable with recommending and initiating treatment for CHC, while PCPs were particularly uncomfortable with those roles. This finding is consistent with other studies on PCP knowledge of new DAAs and comfort level with treatment [6]. The finding highlights the need to educate PCPs with novel and longitudinal educational models if PCPs are to become a source of increased capacity for care in the future.…”
Section: Discussionsupporting
confidence: 90%
“…Specialists were the most comfortable with recommending and initiating treatment for CHC, while PCPs were particularly uncomfortable with those roles. This finding is consistent with other studies on PCP knowledge of new DAAs and comfort level with treatment [6]. The finding highlights the need to educate PCPs with novel and longitudinal educational models if PCPs are to become a source of increased capacity for care in the future.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find a difference in efficacy between GT1a and GT1b patients, but this may be explained by the wide use of RBV. A third issue regarding the high efficacy of SOF/SMV in our population is the fact that patients were treated by hepatologists in referral centres rather than in community‐based practice; this may result in greater treatment adherence, better management of AE and, secondarily, in higher response rates …”
Section: Discussionmentioning
confidence: 99%
“…Thomson et al reported the results of one survey showing that although PCPs identified high‐risk populations for screening, 19% failed to identify age (“Baby Boomer screening”) and dialysis as risk factors. The PCPs surveyed also did not feel up to date with current treatment, and the majority also underestimated efficacy and tolerability, and overestimated treatment duration . Awareness and educational programs for PCPs will be instrumental in implementing and expanding their role.…”
Section: Expanding the Pool Of Treatersmentioning
confidence: 99%
“…It is essential, therefore, to expand the number of health care providers who can treat hepatitis C and expand treatment to more challenging populations. Thomson et al 3 reported the results of one survey showing that although PCPs identified high-risk populations for screening, 19% failed to identify age (''Baby Boomer screening'') and dialysis as risk factors. The PCPs surveyed also did not feel up to date with current treatment, and the majority also underestimated efficacy and tolerability, Abbreviations: DAA, direct-acting antiviral; ECHO, Extension for the Community Healthcare Outcomes; HCV, hepatitis C virus; NP, nurse practitioner; PCP, primary care provider; SVR, sustained virological response.…”
Section: Expanding the Pool Of Treatersmentioning
confidence: 99%
See 1 more Smart Citation